Diallel analysis in white oat cultivars subjected to water stress - Ribeiro,Guilherme (2011)
The goal of this work was to determine the combining ability of three white oat parental genotypes (UPF 18, URS21 and URS 22) and to estimate the heterosis of F1 hybrids in two conditions, with and without water stress. The results indicate a large effect of the environment on the evaluated characters (cycle, leaf area, plant stature, grain yield per plant, main panicle weight and number of grains of the main panicle). The condition without stress was the most efficient for the selection of superior genotypes. Based on the general and specific combining ability, the cultivar URS 22 was shown to be indicated for cycle and stature reduction, while UPF 18 lead to increases in leaf area, main panicle weight and number of grains of the main panicle. The specific cross URS 22 x URS 21 was the best for the selection of superior genotypes.